2013
DOI: 10.1186/1472-6882-13-317
|View full text |Cite
|
Sign up to set email alerts
|

The use of herbal medicines during breastfeeding: a population-based survey in Western Australia

Abstract: BackgroundMain concerns for lactating women about medications include the safety of their breastfed infants and the potential effects of medication on quantity and quality of breast milk. While medicine treatments include conventional and complementary medicines, most studies to date have focused on evaluating the safety aspect of conventional medicines. Despite increasing popularity of herbal medicines, there are currently limited data available on the pattern of use and safety of these medicines during breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
104
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 45 publications
11
104
2
6
Order By: Relevance
“…Similarly, domperidone and metoclopramide were ‘never’ or only ‘rarely’ recommended. Other surveys on galactagogues have reported largely similar findings to those described here 2325,29. However, Swiss respondents seemed to recommend predominantly oxytocin nasal spray, herbals, and homeopathic remedies, whereas Canadian respondents used domperidone as well as herbal remedies,28 indicating differences by geographic region.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, domperidone and metoclopramide were ‘never’ or only ‘rarely’ recommended. Other surveys on galactagogues have reported largely similar findings to those described here 2325,29. However, Swiss respondents seemed to recommend predominantly oxytocin nasal spray, herbals, and homeopathic remedies, whereas Canadian respondents used domperidone as well as herbal remedies,28 indicating differences by geographic region.…”
Section: Discussionsupporting
confidence: 80%
“…The same study reported that 24% of respondents were using herbal medicines for the purpose of increasing breast milk supply and to promote breastfeeding performance, regardless of whether participants had been diagnosed with insufficient milk supply or not [5]. Fenugreek was the most commonly used herbal galactagogue during breastfeeding amongst the survey respondents.…”
Section: Introductionmentioning
confidence: 99%
“…We compared the data gathered during the field study to other ethnobotanical investigations dealing with this subject, and to national and international ethnobotanical literature sources and popular references that considered the traditional uses of wild plants in local cuisines for galactagogue purposes [1,12,23,[28][29][30][31][32]39,[49][50][51][52]. The data obtained (frequency of mention, usage of the parts of the plants, and methods of preparation) were evaluated using the cross-table analysis tool in Microsoft Excel software.…”
Section: Discussionmentioning
confidence: 99%